2021
DOI: 10.46909/journalalse-2021-011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saccharomyces Cerevisiae Feed Supplementation on Haematology and Reproductive Parameters for Algerian Rabbits

Abstract: This study aims at investigating the effect of Saccharomyces cerevisiae (SC) supplementation on reproductive performance, haematological parameters and fertility of rabbits under Algerian conditions. The animals were divided into three groups and received the same feed ration during the experimental period. The control group received a basal diet without feed additives (Group#0) and the two yeast SC groups received 0.3 and 0.6 g/day per head (Group#1 and Group#2, respectively). Semen and blood samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
1
1
Order By: Relevance
“…Similarly, Seyidoglu et al (2013) reported no significant differences in hematological parameters within treatment groups despite observing a slight increase in hematocrit and hemoglobin concentrations in rabbits supplemented with yeast. In contrast, Besseboua and Ayad (2021) found statistically significant differences between the RBCs, HGB, HCT, GCT, and MCV in rabbits receiving graded amounts of SC and the control group. According to Seyidoglu et al (2013), this variance may be due to the various S. cerevisiae concentrations.…”
Section: Blood Hematological Parameterscontrasting
confidence: 68%
See 1 more Smart Citation
“…Similarly, Seyidoglu et al (2013) reported no significant differences in hematological parameters within treatment groups despite observing a slight increase in hematocrit and hemoglobin concentrations in rabbits supplemented with yeast. In contrast, Besseboua and Ayad (2021) found statistically significant differences between the RBCs, HGB, HCT, GCT, and MCV in rabbits receiving graded amounts of SC and the control group. According to Seyidoglu et al (2013), this variance may be due to the various S. cerevisiae concentrations.…”
Section: Blood Hematological Parameterscontrasting
confidence: 68%
“…This result is consistent with recent studies that found probiotics significantly increased total sperm cells and semen volume in the ejaculate of rabbit bucks (Ewuola, 2013 andMymrin et al, 2017). In the same trend, Besseboua and Ayad (2021) noted increases in semen volume, mass motility, and individual motility in the rabbits fed diets supplemented with S. cerevisiae up to 0.6 g/day. Similarly, Emmanuel et al (2019) and Helal et al (2018) found a notable improvement in epididymal sperm characteristics, testicular, sperm concentration, motility and testosterone of rabbit bucks that received SC supplements.…”
Section: Semen Qualitysupporting
confidence: 61%
“…We note from some research works the use of yeast as fortifying in animal feed, in particular, dairy cows using Saccharomyces cerevisiae to improve milk production [39][40][41]. So far we cannot consider this as community adoption, but it will be in the future due to the increasing need and cost of feed.…”
Section: Other Ethnobiological Casesmentioning
confidence: 99%